Species composition and distribution of marine algae at Con Co island, Quang Tri province - Dam Duc, Tien; Nguyen Thi, Mai Anh; Nguyen Manh , Linh; Cao Van , Luong; Pham Van , Chien (Vietnam Journal of Marine Science and Technology, 2021)
This paper presents results on species composition and distribution of marine algae at 6 transects of Con Co islands in May 2020. The result of studies shows that 95 species of marine algae are recorded in the study area, belonging to four divisions: Cyanophytes, Rhodophytes, Ochrophytes and Chlorophytes. Among them, five (5) species are classified into Cyanophytes (comprising 5.3% of total species); forty one (41) species into Rhodophytes (43.1%); twenty-nine (29) species into Ochrophytes/Phaeophytes (30.5%) and twenty (20) species into Chlorophytes (21.1%). The species composition of marine algae in Con Co shows significant differences as follows: 48 species (transect number I) to 72 species (transect number IV) and the average value is 60.7 species per transect. Sørensen similarity coefficient fluctuates from 0.56 (transects number I and II) to 0.81 (transects number II and IV, number III and IV) and the average value is 0.70. The current investigations show that twenty-two (22) species are distributed the littoral zone (22.9% of total species) only and thirty-seven (37) species in the sub-littoral zone only. In which there are thirty six (36) species distributed in both littoral zone and sub-littoral zone (44.8%). The algal flora in Con Co is characterized by subtropics.